Simbol Diskursif dan Presentasional Dalam Video Clip Tongtolang Sambasunda - Anggit Surya Jatnika (PANTUN, 2017)
Video clip is one of symbolic media functioning to deliver information to public. The research focuses on analysing the audio visual of Sambasunda’s video clip Tongtolang. The research aims to uncover the discursive and presentational symbol of Sambasunda’s video clip Tongtolang. The research applies Susanne K. Langer’s symbolic approach that is discursive and presentational. Discursive symbol is analyzed through music, lyric, and the visual of Sambasunda’s video clip Tongtolang. The presentational symbol is analyzed through the whole discursive symbols in the video clip. The result of the analysis shows that discursive and presentational symbol of Sambasunda’s video clip Tongtolang is a paradox expression of the Tongtolang lyric. When the character Bapa in the video clip practices or falls down to the polygamy, he actually goes up because of geting the girl he wants. The man falls to the above, meaning that he denies the truth he has been holding. He tries to fnd ‘the way to the above’. He actually goes up when he falls down.Keywords: Discursive and presentational symbol, video clip, tongtolang, Sambasunda